Community Participatory Tools for Water Logging Vulnerability Assessment in Chittagong City Corporation Area - Islam, Md Kamrul; Chowdhury, Sudipta; Chisty, Kutub Uddin; Rahman, Ataur (Journal of Bangladesh Institute of Planners, 2015)
Chittagong city is the second largest metropolitan city of Bangladesh comprising hills with natural landscape on the Bay of Bengal. Water logging is one of the most prominent natural hazards for the city. Heavier than usual rains at the time of May to August results in water logging in many areas of Chittagong. Water logging has been disrupting livelihoods of thousands of people in Chittagong during past two decades. Badurtola is one of the places that is faced with water logging almost every year. Badurtola is prone to water logging due to the vulnerable geographical settings, mismanagement of waste and improper drainage. This research tried to identify the social, physical, and economic vulnerabilities that are causing adverse environmental condition. Necessary data has been collected through different participatory tools, which includes social map, resource map, cause effect diagram, daily activity schedule, process map, Venn diagram, service opportunity map etc. The target groups of this research are the persons, who live in the slums as they are the mostly affected and also the other groups in the society. Major findings revealed the causes of water logging are due to the dumping of waste in the drain, mismanagement of drain and also for the narrow drainage due to encroachment of drain for construction. The study found that most vulnerable groups due to the water logging are children and office going people. Some recommendations are made in the paper on the basis of the opinion of the local people, such as facilitating drainage, provision of dustbins and waste collection system, cleaning of drains and widening of drains and proper management of the drains. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 221-231